2023
DOI: 10.3233/jad-230097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pathway-Specific Polygenic Risk Scores for Alzheimer’s Disease (AD) on Rate of Change in Cognitive Function and AD-Related Biomarkers Among Asymptomatic Individuals

Abstract: Background: Genetic scores for late-onset Alzheimer’s disease (LOAD) have been associated with preclinical cognitive decline and biomarker variations. Compared with an overall polygenic risk score (PRS), a pathway-specific PRS (p-PRS) may be more appropriate in predicting a specific biomarker or cognitive component underlying LOAD pathology earlier in the lifespan. Objective: In this study, we leveraged longitudinal data from the Wisconsin Registry for Alzheimer’s Prevention and explored changing patterns in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Similar age-related trajectories were observed for non-APOE PRS; however, the effect emerged approximately a decade later than the APOE effect. 7 These findings are consistent with recent studies using Alzheimer's Disease Neuroimaging Initiative (ADNI) and UK Biobank (UKBB) data, concluding that both APOE and non-APOE PRS predicted LOAD risk and presented agerelated effects, but the APOE effects were stronger among individuals younger than 80 years of age, whereas the non-APOE PRS effects were stronger for those older than 80 years of age. 8 In addition to age-related genetic effects, it has been shown that the contribution of non-APOE PRS to LOAD also differs according to APOE ε4 carrier status; however, such findings are not consistent.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar age-related trajectories were observed for non-APOE PRS; however, the effect emerged approximately a decade later than the APOE effect. 7 These findings are consistent with recent studies using Alzheimer's Disease Neuroimaging Initiative (ADNI) and UK Biobank (UKBB) data, concluding that both APOE and non-APOE PRS predicted LOAD risk and presented agerelated effects, but the APOE effects were stronger among individuals younger than 80 years of age, whereas the non-APOE PRS effects were stronger for those older than 80 years of age. 8 In addition to age-related genetic effects, it has been shown that the contribution of non-APOE PRS to LOAD also differs according to APOE ε4 carrier status; however, such findings are not consistent.…”
Section: Introductionsupporting
confidence: 90%
“…First, the observed interaction between age, PRS, and APOE might be driven by the established Alzheimer's biological pathways, such as cholesterol metabolism, endocytosis, and immune response, of which APOE is included in the majority of these pathways. 7 However, in the current study, we only focus on the preclinical cognitive function as the outcome but have not extended the study to AD‐related biomarkers because of the concern for the balance between model complexity and sample size (biomarker samples usually have small sample sizes, N < 200). The absence of information from the study of those endophenotypes limits our ability to interpret the biological nature behind the observed interaction effects.…”
Section: Discussionmentioning
confidence: 99%
“…Past epidemiological studies have investigated how lifestyle choices affect the genetic risk of LOAD, yielding mixed results 15,16,39,40 , with some null findings even in a large sample 15 . Recent research has demonstrated that age modifies LOAD genetic risk 18,41,42 and that PRS effects on LOAD-related traits are stronger among APOE-ε4 carriers 22,[43][44][45] . However, these findings have not been integrated into previous genelifestyle interaction analyses, as the present analysis does.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been hypothesized that a healthy lifestyle may mitigate the adverse genetic effect, existing studies have yielded mixed results 13,[15][16][17] . In our earlier work, we found that the effects of APOE and non-APOE PRS are age-related, and the genetic burden of the non-APOE PRS is more detrimental among APOE-ε4 carriers than among noncarriers 18,19 . These findings indicate that the risk modifying effect of nongenetic protective factors on non-APOE PRS may be best detected among APOE-ε4 carriers.…”
Section: Introductionmentioning
confidence: 89%